Experimental ischaemic stroke induces transient cardiac atrophy and dysfunction. Issue 1 (30th October 2018) - Veltkamp, Roland; Uhlmann, Stefan; Marinescu, Marilena; Sticht, Carsten; Finke, Daniel; Gretz, Norbert; Gröne, Herrmann‐Josef; Katus, Hugo A.; Backs, Johannes; Lehmann, Lorenz H.
Abstract: Background: Stroke can lead to cardiac dysfunction in patients, but the mechanisms underlying the interaction between the injured brain and the heart are poorly understood. The objective of the study is to investigate the effects of experimental murine stroke on cardiac function and molecular signalling in the heart. Methods and results: Mice were subjected to filament‐induced left middle cerebral artery occlusion for 30 or 60 min or sham surgery and underwent repetitive micro‐echocardiography. Left ventricular contractility was reduced early (24–72 h) but not late (2 months) after brain ischaemia. Cardiac dysfunction was accompanied by a release of high‐sensitive cardiac troponin (hsTNT (ng/ml): d1: 7.0 ± 1.0 vs. 25.0 ± 3.2*; d3: 7.3 ± 1.1 vs. 52.2 ± 16.7*; d14: 5.7 ± 0.8 vs. 5.2 ± 0.3; sham vs. 60 min. MCAO; mean ± SEM; * p  < 0.05); reduced heart weight (heart weight/tibia length ratio: d1: 6.9 ± 0.2 vs. 6.4 ± 0.1*; d3: 6.7 ± 0.2 vs. 5.8 ± 0.1*; d14: 6.7 ± 0.2 vs. 6.4 ± 03; sham vs. 60 min. MCAO; mean ± SEM; * p  < 0.05); resulting from cardiomyocyte atrophy (cardiomyocyte size: d1: 12.8% ± 0.002**; d3: 13.5% ± 0.002**; 14d: 6.3% ± 0.003*; 60 min. MCAO vs. sham; mean ± SEM; ** p  < 0.01; * p  < 0.05), accompanied by increased atrogin‐1 and the E3 ubiquitin ligase murf‐1. Net norepinephrine but not synthesis was increased, suggesting a reduced norepinephrine release or an increase of norepinephrine re‐uptake, resulting in a functional denervation. Transcriptome analysis in cardiac tissue identified the transcription factor peroxisome proliferator‐activated receptor gamma as a potential mediator of stroke‐induced transcriptional dysregulation involved in cardiac atrophy. Conclusions: Stroke induces a complex molecular response in the heart muscle with immediate but transient cardiac atrophy and dysfunction.